Abordagem Pikler: contribuições para a formação permanente de professores e professoras que trabalham com crianças, do nascimento aos três anos de idade, em contexto de creche - Ginante, Andréia (2022)
This Master’s in Education research: Curriculum is situated in the field of “Continuing Education for Teachers – The Nursery Education and Play” and it draws from my experience as a practitioner in early childhood education, working with children and adult caregivers, as well as from academic research on early childhood. The literature review conducted uncovered the academic production of Dr Emmi Pikler, a Hungarian pediatrician who developed theory based on practices derived from education and care of newborns and young children. This study’s main objective is to introduce the Pikler’s approach, its principles, and its contributions to the praxis of teachers that support children since birth until 3 years of age in nursery schools. Furthermore, its specific objectives are a) Provide references that advance the understanding of the foundational elements of the Pikler’s approach; b) Contribute to the Piklerian research ethics and practice; and c) Propose a continuous education program for teachers in nursery schools based on the praxis put forward by the Pikler Institute. As a qualitative study, leveraging literature and document reviews, the research method spanned from theoretical as well as primary sources of information such as video footage and photography archived by the Pikler Institute. It draws from the piklerian principles put forward by Emmi Pikler (2009) and scholars who developed theory in close collaboration with her propositions: Anna Tardos (2010), Geneviève Appell and Myrian David (2021), Judit Falk (2021), Éva Kálló and Gyórgyi Balog (2017), Agnès Szanto Feder (2014) and scholars who researched continuing education: Francisco Imbernón (2011), Maurice Tardif (2014), Marcelo García (1999), Marina Graziela Feldmann (2009), Maria Alice Proença (2018), Neide de Aquino Noffs (2002), among others. Moreover, this research was conducted leveraging learnings from the Pikler development program for Pedagogue, CERTIFIED PIKLER® PROFESSIONAL offered by the Institute Pikler in Budapest, and its contribution is to put forward a proposal for continuous education program for teachers, aiming at enabling them to introduce attainable and required change in their practices